A fast automated screening method for the detection of blood transfusion in sports. Issue 11 (22nd May 2014) - Leuenberger, Nicolas; Ansermet, Camille; Pottgiesser, Torben; Baume, Norbert; Robinson, Neil; Saugy, Martial; Schumacher, Yorck Olaf
<x xml:space="preserve">Abstract</x> Currently, there is no simple direct screening method for the misuse of blood transfusions in sports. In this study, we investigated whether the measurement of iron in EDTA‐plasma can serve as biomarker for such purpose. Our results revealed an increase of the plasma iron level up to 25‐fold 6 h after blood re‐infusion. The variable remained elevated 10‐fold one day after the procedure. A specificity of 100% and a sensitivity of 93% were obtained with a proposed threshold at 45 µg/dL of plasma iron. Therefore, our test could be used as a simple, cost effective biomarker for the screening for blood transfusion misuse in sports. Copyright © 2014 John Wiley & Sons, Ltd.